Budaya merokok pada wanita di Suku Tengger - Luqman Afifudin; Fatwa Sari Tetra Dewi; Retna Siwi Padmawati (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Smoking behavior culture of Tenggerese women Purpose: Number of female smokers continues to increase. Most of Tenggerese women who lived in Lumajang district have smoking habit. This study aims to describe the cultural smoking behavior of Tenggerese women.Methods: This was a qualitative research with ethnography approach. The informant was obtained through snowball method based on information from local leader and health cadre, then the informant was chosen used purposive method based on predetermined inclusion criteria. The main informant was 9 Tenggerese women who smoke. Additional informants consist of 13 people consisting of 8 informant’s husband and 5 local leader, shaman, local public figure, midwife, and agricultural officer. Data collection was done by in-depth interview and observation.Results: Cigarettes become one of the material offerings Gedang Ayu or Pitrah. Argosari village is the village of Kalapatra which means having a difference in place, time, and habits have implications on the culture or habits of Tenggerese in terms of smoking so that smoking is a common thing in women and seems not found on other district. The gender perspective in meet with economic needs of the family is a factor supporting women to have smoking habits. The socio-cultural aspects prevailing in society encourage the Tenggerese women’s smoking behavior. Informants know the cigarette and its impact from health warning pictures on cigarette pack. Health promotion efforts in tobacco control are undertaken by health workers through the activities of the Birth Planning Program and prevention of complications (P4K) and school health (UKS).Conclusions: Cigarettes became part of the Tenggerese culture in Argosari Village. Behavior of smoking into Tengger women’s culture and smoking is common place because Argosari Village is Kalapatra Village. But nowadays, many teenage women do not smoke anymore include all pregnant women in young age. People who are respected in the community such as village leader, traditional healers , and community leaders also do not smoke. Perspectives of gender and socio-cultural aspects prevailing in Tengger society are contributing factors to the Tenggerese women’s smoking behavior.